An Enantioselective Synthesis of Spirobilactams through Copper‐Catalyzed Intramolecular Double N‐Arylation and Phase Separation. (23rd July 2015) - Liu, Jianguang; Tian, Yingying; Shi, Jialing; Zhang, Shasha; Cai, Qian
Abstract Spirobicyclic structures are versatile building blocks for functional chiral molecules. An enantioselective synthesis of chiral spirobilactams via a copper‐catalyzed double N‐arylation was developed. Amplification of solution ee by in situ precipitation of the racemate was observed with this method and enantioenriched spirobilactams were obtained with excellent ee values through simple solid–solution phase separation.